The Engineers' Engineer: Sir John Kennedy and the Port of Montreal - White, Richard (Scientia Canadensis, 2003)
AbstractThis article gives an overview and analysis of the career of Canadian civil engineer Sir John Kennedy (1838-1921), and comments on what Kennedy's career reveals of the professional ideals of early twentieth century engineering. Kennedy was a highly regarded engineer in his day. He served as an early President of the Canadian Society of Civil Engineers (CSCE) in 1892 and is one of the few Canadian engineers to have been knighted. Kennedy spent most of his working life as Chief Engineer of the Montreal Harbour Commission, in which capacity he oversaw the deepening of the St Lawrence River channel from Quebec to Montreal and a complete reconstruction of the Montreal harbour—two projects that essentially made the modern Port of Montreal. The study provides details of these construction jobs and of Kennedy's role in the work. So well regarded was Kennedy by his peers that shortly after his death the CSCE named its highest professional award after him, making him literally a professional icon. The author takes this to indicate that Kennedy's professional style and values—congenial, practical, and public-spirited—evidently embodied the professional ideals of the time.